Biocultural Significance of Plant Diversity in the Afadjato Community Forest Conservation Area - Kwaku, D.G.F. (University of Ghana, 2012)
The study was undertaken in the Afadjato Community Forest Conservation Area between August 2010 and June 2011 with the following objectives: 1. To document and analyse the diversity of plants in the Afadjato Community Forest Conservation Area. 2. To undertake a quantitative ethnobotanical study of traditional knowledge and plant use among local people living in the study area. 3. To explore the relationship between plant diversity and use; and 4. To determine the conservation and ecotourism implications of the study on the future of Afadjato as a conservation and ecotourism site . The ethnobotanical information was collected through semi-structured questionnaire interviews administered to 133 informants (age range 40-80 years, mean age of 55 years). The interviews were conducted in the informant‟s homes thereby covering a total of 28 households out of the 159 households in the three communities studied. The questionnaire sought for information on age and gender of the respondents, which plant parts are harvested and used, where they are collected, and cultivation status of the plants. This data was analysed using the following parameters: Informant Consensus Factor (F ic ), Use-Value (UV), and Fidelity Level (FL) of the species. Sampling points of 100 m apart from the bottom of the hill to the summit were established along three transects. At each point, plots measuring 25m x 25m, 5m x 5m, and 1m x 1m were demarcated giving 96 plots in all. Trees with Girth at Breast Height (GBH≥10cm) were identified, counted and heights determined in the 25m x 25m plots. Shrubs with (GBH≥3cm) were recorded in the 5m x 5m plots, and herbs were recorded on the 1m x 1m plots. The data obtained was analysed using the following parameters: Density, Relative density, Frequency, and Relative frequency. Species diversity was expressed as Shannon diversity index and Shannon diversity index. A total of 166 plant species belonging to 53 families were identified as mostly used by the people in the following use-categories: Building (25.2%), Human food (23.3%), Household items (19.9%), Fuelwood (15.8%), and Medicine (15.8%). The plant families Fabaceae, Apocynaceae and Euphorbiaceae provided most of the plant parts used by the communities around the study site. Trees were the most widely used group. The stem was the plant part mostly used by the people. The F ic values of the present study ranged from (0.52-0.68) indicating that there was a high agreement in the use of plants in all the use-categories under consideration among users. Out of the 169 reported plants species, 99 of them had the highest fidelity level (FL) of 100%. The most important species according to their use-values was Khaya species (0.86). A total of 269 species (trees 100, shrubs 96, and herbs 73) were present in a total of 96 plots (25m x 25m (30), 5m x 5m (33), and 1m x 1m (33)) established along 3 transects. The Fabaceae family had the most represented species in the trees, shrubs and the herbs. The mean stand density of all the species present in the study site was 3.38 ±0.09. The Shannon diversity was lower in the herbs (0.81) than the shrubs (0.86) but decreased again in the trees (0.81). In a similar vein the Simpson‟s diversity for the herbs, shrubs, and trees was (-0.05), (3.48), and (1.06) respectively inferring that the study site has relatively high plant species diversity. There was a decrease in diversity of herbs, shrubs and trees with altitude in all the three transects. This trend was also seen in the westwards to eastwards direction. Herbaceous species that occurred in all the 3 transects include: Griffonia simplicifolia, Phaulopsis parviflora and Smilax longiflora. Shrubs that occurred in all the 3 transects include: Byrsocarpus coccineus, Chromolaena odorata, Lophira lanceolata, Mallotus oppositifolia, Olax subcorpioides, Pterocarpus malbraedii, Sterculia tragacantha and Carpolobia lutea. It was observed that 65 tree species were relatively small and had a Girth at Breast Height of between 10cm-70cm. They included: Albizia sp, Argocoffeopsis rupestris, Securidaca longiflorum, and Sterculia sp. The range of tree species count per 25m x 25m plot was from 6 to 16 and the mean tree height recorded in this study was 19.12m. Twenty-two tree species occurred in all the 3 transects studied and included: Albizia spp, Baphia pubescens, Bridelia ferruginea, Cola spp, Crossopterix febrifuga, Dacleodes kleineana and Dialium guineense among others. It is suggested that the plant families Fabaceae, Apocynacece and Euphorbiaceae should be closely monitored to guarantee their sustainable use in the light of their intense utilization by the people of the study area. This monitoring exercise can provide insights for the development of policies and practice that may help to prevent comparable levels of forest loss and degradation elsewhere in the country through unsustainable use.
Thesis (MPHIL) - University of Ghana, 2012